Resistance and Fight Against Oppression and Patriarchy: Investigatingthe Subjugated Voices of Subaltern in the Skyfall (Journal of Asian Development Studies, 2023)
The current study explores the plight, troubles, and struggle of subalterns and their endeavors toraise their voices against the injustice incurred upon them in the novel Skyfall by award-winningPakistani author Saba Karim Khan. The current study focuses on subaltern studies and employsthe theoretical framework of postcolonial theory. The study aims to indicate ways to fulfill twopurposes in which subalterns, particularly female characters, are being marginalized andsuppressed due to the power structure of social and cultural factors and the misappropriation ofreligious teachings, gender, and sexuality. Secondly, it identifies the resistance and fight againstoppression and patriarchy. The study is qualitative and uses the text as a primary source of datacollection, which is analyzed in the light of Gayatri Spivak's essay “Can the Subaltern Speak?”Saba Karim Khan has beautifully interwoven themes of oppression, marginalization, gender, andsexuality in the text and portrayal of social, political, economic, and religious forces in shapingthe power structure. Data analysis shows that oppression and marginalization are evident throughthe subaltern characters of protagonist Rania Mirza Kasturi, her mother Jahaan e Rumi, and hersister Ujala. On the other hand, textual evidence from the novel demonstrates that these charactersdo not always remain silent victims and raise their voices against tyrannical forces to acquire theiridentity as individuals